Biopsychosocial factors associated with physical activity among Resettlers of the former Soviet Union in Germany: a cross-sectional analysis - Ouma, Mary; Juma, Kenneth; Meisinger, Christa; Stolpe, Susanne; Becher, Heiko; Winkler, Volker; Deckert, Andreas (BMJ open, 2024)
Objective Previous research suggests an overall lower cardiovascular disease mortality among ethnic German Resettlers from the Former Soviet Union. However, evidence points to a high burden of metabolic risk factors and chronic conditions among Resettlers, factors which are correlated to lower levels of physical activity. Thus, this study aims to assess factors associated with physical activity among Resettlers, by investigating the interplay between biopsychosocial factors and physical activity between men and women. - Design We conducted a cross-sectional study by administering questionnaires between 2011 and 2012. Data from 595 individuals were analysed, and total and extracurricular physical activity scores were generated. A backward stepwise linear regression was run to investigate the effect of various predictors on various physical activity domains. - Setting Augsburg, Germany. - Participants We targeted Resettlers who had moved to Augsburg, Germany between 1990 and 1999. - Results Disease and psychological distress were linked to decreasing physical activity in men. Higher socioeconomic status was correlated with increasing physical activity except for work-related physical activity for both men and women. Single women were less likely to report extracurricular activity, and so did women who reported a shorter duration of stay and men who smoked. - Conclusions Migration experience and culture account for gender-related sex differences in physical activity alongwith other interlocking social factors such as psychological stressors and health status among Resettlers. Individual psychological stressors may hinder or motivate physical activity, but physical activity can reverse the influence of such stressors on Resettlers. Understanding migrant health and experiences is crucial due to the migration influx and health disparities. However, data on this topic are scarce in Germany.